Synergistic and Additive Antimicrobial Activities of Curcumin, Manuka Honey and Whey Proteins. Issue 5 (15th February 2016) - Balan, Prabhu; Mal, Gorakh; Das, Shantanu; Singh, Harjinder
Abstract: Antimicrobial activity of curcumin, Manuka honey (MH, Leptospermum scoparium ) and Whey protein isolate (WPI) and their synergistic and/or additive effects were tested against various Gram positive and negative bacterial strains for development of functional foods. Curcumin and MH each displayed 100% inhibition against all the tested strains of bacteria. The minimum inhibitory concentration values of curcumin and honey against different strains ranged from 100 to 250 µg/mL and 5–20% respectively. Except Bacillus subtilis, all other tested pathogens were completely inhibited by the mixture of subinhibitory concentrations of curcumin and MH. At these levels, the mixture of MH and WPI was more effective against Streptococcus pyogenes, Shigella soneii and Proteus vulgaris . Mixture of curcumin and WPI completely inhibited the growth of Listeria monocytogenes and Staphylococcus aureus . Combinations of curcumin, MH and WPI had additive and/or synergistic antimicrobial activities and various combinations could be used in food formulations and pharmacological applications. Practical Applications: Turmeric, honey and whey proteins are widely consumed all over the world, and have been associated with multiple health benefits. Synergistic and/or additive antimicrobial effects of curcumin, Manuka honey (MH) and whey protein isolate (WPI) were tested against various Gram positive and negative bacterial strains for development of functional foods. Curcumin and MH each showed complete inhibition against all the tested bacterial strains. These in vitro investigations demonstrate that combinations of curcumin, MH and WPI have potent antibacterial activities. To our knowledge, this is the first of such outcomes to be reported. The implication of the results of this study is that Curcumin, MH and WPI in various combinations could be used as a food supplement and also in pharmacological applications.